2018 Academic Emergency Medicine Consensus Conference: Advancing Pediatric Emergency Medicine Education Through Research and Scholarship. (12th November 2018) - Klig, Jean E.; Fang, Andrea; Fox, Sean M.; Hom, Jeffrey; Strobel, Ashley; Tat, Sonny; Wall, Jessica J.; Bhat, Rahul; Weinberg, Eric; Deninghoff, Kurt R.; Ishimine, Paul; Kou, Maybelle
Abstract: To achieve high‐quality emergency care for pediatric patients nationwide, it is necessary to define the key elements for pediatric emergency medicine (PEM) education and scholarship that would: 1) close the gaps in fundamental PEM education and 2) promote systems and standards that assure an ongoing communication of best practices between tertiary pediatric institutions, general (nonchildren's) hospital emergency departments, and urgent care centers. A working group of medical educators was formed to review the literature, develop a framework for consensus discussion at the breakout session, and then translate their findings into recommendations for future research and scholarship. The breakout session consensus discussion yielded many recommendations. The group concluded that future progress depends on multicenter collaborations as a PEM education research network and a unified vision for PEM education that bridges organizations, providers, and institutions to assure the best possible outcomes for acutely ill or injured children.